Integrating Sports Massage into Pre-training Routines Can Enhance Athletic Preparedness and Performance Capacity in Kabaddi Players - Isnandar, Muhammad; Alhumary, Farid M.; Krzykarist, Krzykarist; Zega, Restin; Hutajulu, Reymond Benedith; Putri, Rachel Junika Abelia; Hofmeister, Martin (INSPIREE: Indonesian Sport Innovation Review, 2025)
The  purpose  of  the study. The primary objective of this investigation is to assess the efficacy of pre-training sports massage in enhancing warm-up protocols for kabaddi athletes, focusing on its influence on various physiological parameters, performance metrics, and psychological preparedness. Materials and methods. A quasi-experimental design was employed involving a cohort of 20 elite kabaddi athletes (15 males and 5 females) aged between 18 and 30 years, hailing from professional teams in Medan City. The intervention spanned 8 weeks and consisted of a 15-minute pre-training sports massage regimen administered prior to standard warm-up sessions. Data were collected at baseline, after 4 weeks, and following 8 weeks of intervention, encompassing measurements of muscle temperature, range of motion, reaction time, performance indicators, and perceived readiness, utilizing standardized assessment instruments. Results. The intervention yielded statistically significant enhancements across multiple evaluated parameters. Muscle temperature exhibited an average increase of 2.3°C, while range of motion demonstrated a 12.5% improvement in hip flexibility; additionally, performance metrics revealed a 22% augmentation in defensive maneuver efficiency. Reaction time was reduced by 0.3 seconds, and participants indicated a decrease in perceived exertion alongside an enhancement in psychological readiness. All observed improvements were statistically significant (p < 0.001) and characterized by large effect sizes. Conclusions. The implementation of pre-training sports massage emerges as a potentially beneficial intervention for the optimization of warm-up protocols among kabaddi athletes. The extensive advantages noted across physiological, biomechanical, and psychological realms imply that the incorporation of sports massage into pre-training routines may significantly bolster athletic preparedness and performance capacity, particularly in high-intensity contact sports such as kabaddi.